Włączenie karty adresowej zabytku nieruchomego do gminnej ewidencji zabytków. Refleksje na tle materialnej definicji zabytku i najnowszego orzecznictwa sądów administracyjnych - Główczewska, Aleksandra (PRAWO i WIĘŹ, 2025)
This paper aims to analyse the implications of including an address card for an immovable monument in the municipal monuments register. This is considered in the context of the material definition of a monument and the latest administrative court case law. The study presents two perspectives on the entry of monuments into the municipal register, as reflected in legal doctrine and case law. It also examines the role of the Constitutional Tribunal’s ruling of 11 May 2023 (case no. P 12/18) concerning the inclusion of an immovable monument’s address card in the register, along with the impact of this judgment on subsequent rulings by administrative courts.